Hubungan Tingkat Risiko Musculoskeletal Disorders (MSDs) Mengguna-kan Rapid Entire Body Assessment (REBA) dengan Keluhan MSDs pada Residen Ilmu Bedah - Tubagus, Ade P.; Doda, Diana V. D.; Wungouw, Herlina I. S. (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: According to WHO, musculoskeletal disorders are categorized as the second rank of work-related disease. Various factors such as work, individual, and social factors can cause MSDs. These disorders play an important role in morbidity of workers such as healthcare workers. This study was aimed to analyze the correlation between the risk level of MSDs evaluated by using REBA and MSDs complaints among surgery residents. This was an analytical observational study with a cross-sectional design. The instruments used in this study were the Rapid Entire Body Assessment (REBA) worksheet and the Nordic Body Map (NBM) questionnaire. Data were analyzed with the Spearman correlation test. There were 42 surgery residents of Faculty of Medicine, Sam Ratulangi University, Manado participated in this study. The majority of them were males (81%) and young adults (88%). The prevalence of MSDs complaints were as follows: 60% of respondents had mild complaints, 33% had moderate complaints, and 7% had severe complaints. The bivariate analysis showed that the risk level of MSDs evaluated by REBA had a strong positive correlation with MSDs complaints (P=0.000; r=0.603). Conclusion: There was a significant correlation between risk level of MSDs evaluated by using REBA and the MSDs complaints. Based on the results, ergonomics interventions are recommended to surgery residents in order to prevent the occurence of MSDs.Keywords: musculoskeletal disorders (MSDs), REBA, surgery residentsAbstrak: Musculoskeletal disorders (MSDs) menurut WHO berada di urutan kedua terbanyak penyakit akibat kerja. Berbagai faktor seperti pekerjaan serta faktor individu dan sosial dapat menyebabkan terjadinya MSDs. Gangguan ini berperan dalam morbiditas di banyak bidang pekerjaan salah satunya di bidang kesehatan. Penelitian ini bertujuan untuk mengetahui hubungan tingkat risiko MSDs menggunakan REBA dengan keluhan MSDs pada residen ilmu bedah. Jenis penelitan ialah analitik observasional dengan desain potong lintang. Alat ukur yang digunakan ialah lembar kerja Rapid Entire Body Assessment (REBA) dan kuesioner Nordic Body Map (NBM). Analisis data menggunakan uji korelasi Spearman. Hasil penelitian mendapatkan sebanyak 42 residen ilmu bedah Fakultas Kedokteran Universitas Sam Ratulangi Manado menjadi responden penelitian. Mayoritas responden berjenis kelamin laki-laki (81%) dan berada dalam kategori dewasa muda (88%). Prevalensi keluhan MSDs ialah 60% keluhan MSDs ringan, 33% keluhan sedang, dan 7% keluhan berat. Hasil uji korelasi Spearman mendapatkan tingkat risiko MSDs menggunakan REBA memiliki hubungan positif kuat dengan keluhan MSDs (P=0,000, r=0,603). Simpulan: Terdapat hubungan bermakna antara tingkat risiko MSDs menggunakan REBA dengan keluhan MSDs. Berdasarkan hasil penelitian maka direkomendasikan intervensi ergonomi pada residen bedah untuk mencegah terjadinya keluhan MSDs.Kata kunci: musculoskeletal disorders (MSDs), REBA, residen bedah